Scleral Buckling and Corneal Topography in a Rare Case of Keratoconus with Rhegmatogenous Retinal Detachment in an Indian Patient - Kalpana, B N; Shilpa, Y D; Prabhakar, Sneha Priya; Prakash, S M Ram; Hemalatha, B C; Ravi, B; Devaru, Sheetal (Nepalese Journal of Ophthalmology, 2018)
Background: Management of Rhegmatogenous Retinal Detachment (RRD) in keratoconus could be challenging in various aspects. Visualisation of fundus due to altered reflex along with axial myopia could pose difficulty while performing pars plana vitrectomy. Our patient underwent Scleral Buckling with good anatomical results. We came across an isolated case of Keratoconus with Retinal detachment without any pre existing comorbidities unlike earlier reports where patients with history of atopic dermatitis had Keratoconus associated with RRD. The main purpose was to know the outcome of scleral buckling and its effect on corneal topography in a case of keratoconus with RRD.Case: A 35 year old female presented with diminution of vision in both eyes since childhood, but more so in the right eye (RE) since last 6 months. She was aphakic with VA of 1/60 and 2/60 in the right and left eye respectively. She was diagnosed as both eyes keratoconus with RE near total rhegmatogenous retinal detachment (RRD) with sub retinal gliosis. She gave no history of vigorous eye rubbing or atopic dermatitis. For RE she underwent uneventful scleral buckling surgery.Observation: In post operative follow up, the retina was attached. Placido based corneal topography was done pre operatively with keratometry reading of RE – K1 62.79@96º, K2 – 55.92@6˚ and repeated at the end of three months follow up with readings of RE – K1-61.45@98˚, K2- 54.50@ 8˚. There were minimal changes in the keratometry values post operatively with flattening of vertical meridian and horizontal meridian.Conclusion: In keratoconus, RD can occur without any predisposed or preceding condition. Although majority of cases are associated with atopic dermatitis and eye rubbing. Scleral buckling (SB) was successful with good functional and anatomical outcome., however it has minimal effect on corneal topography.